주가지수 방향성 예측을 위한 도메인 맞춤형 감성사전 구축방안 - 김재봉(Jae-Bong Kim); 김형중(Hyoung-Joong Kim) (디지털콘텐츠학회논문지, 2017)
개인용 디바이스의 발달로 개인들이 손쉽게 인터넷에 접속할 수 있게 되었으며, 소셜미디어를 통한 정보의 공유와 습득이 일반화 되고 있다. 특히 분야별 전문 커뮤니티가 발달하며 사회적 영향력을 행사하고 있어 기업과 정부는 이들의 의견을 반영하여 전략을 수립하는 일에 관심을 기울이고 있다. 온라인상의 다양한 텍스트로부터 대중의 의견을 읽어내는 것을 오피니언마이닝이라고 한다. 그 중 하나인 감성사전은 방대한 비정형데이터를 빠르게 파악하는 도구로 여러 분야에서 활용되고 있다. 주식시장은 사회의 여러 요인을 반영하여 변동한다. 최근에는 버즈량 분석 등 빅데이터를 기반으로 오피니언마이닝을 활용한 주식시장 연구가 시도되고 있다. 대표적인 예로 뉴스와 같은 텍스트 데이터 분석을 활용한 연구들이 발표되고 있다. 본 논문에서는 뉴스의 정제된 형식과 한정된 어휘를 사용한 기존연구를 보완하고자 증권전문 사이트 ‘Paxnet’의 게시 글을 분석대상으로 삼아 주식시장 맞춤형 감성사전을 구축하여 투자자들의 감성을 분석하는 데 기여했다. As development of personal devices have made everyday use of internet much easier than before, it is getting generalized to find information and share it through the social media. In particular, communities specialized in each field have become so powerful that they can significantly influence our society. Finally, businesses and governments pay attentions to reflecting their opinions in their strategies. The stock market fluctuates with various factors of society. In order to consider social trends, many studies have tried making use of bigdata analysis on stock market researches as well as traditional approaches using buzz amount. In the example at the top, the studies using text data such as newspaper articles are being published. In this paper, we analyzed the post of ‘Paxnet’, a securities specialists’ site, to supplement the limitation of the news. Based on this, we help researchers analyze the sentiment of investors by generating a domain–specific sentiment lexicon for the stock market. KCI Citation Count: 14